The understanding of spirituality among Muslim patients with depression - Md. Rosli, Ahmad Nabil; Mohamed Saini, Suriati; Jahan, Nasrin; Bahari, Rafidah; Sarip, Salisah (2015)
Introduction: The mainstay of treatment of depression and trauma-related psychological problems relies on pharmacological and psychological treatments. On top of that, evidences also recognize the vital role of spirituality for human wellness which leads to growing interest on its utilization to treat depression. However, research on spirituality among Muslims in relation to depression is relatively scarce. The aim of this study is to explore Muslim patients’ understanding of spirituality and factors influencing their preference to spiritual treatment to complement modern treatment.